2016
DOI: 10.3171/2015.1.jns141301
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomized trial on the clinical effect of different shunt valve settings in idiopathic normal pressure hydrocephalus

Abstract: However, complications following shunt surgery are common, 11,16 especially subdural hematoma (SDH) seen in 2%-21% of iNPH patients treated with VP or VA shunts. 7,8,15,21 Adjustable valves that permit the opening pressure to be changed externally have been recommended as a means of reducing the complication rate and enabling clinicians to optimize individual treatment. 1,2Randomized studies have indicated that lower opening pressure is related to better outcome 5 but also to more overdrainage symptoms, 6 SDH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…Of note, this latter group also improved after opening the shunts, although with less benefit (28 and 18%, respectively) [39].This rate of benefit is in line with the results of a systematic review, which reported a long-term response of 29% [40]. A double-blind randomized trial on the clinical effect of different shunt valve settings was also performed [41]; improvement after shunt surgery was evident within 3 months, irrespective of valve setting.…”
Section: Managementsupporting
confidence: 79%
“…Of note, this latter group also improved after opening the shunts, although with less benefit (28 and 18%, respectively) [39].This rate of benefit is in line with the results of a systematic review, which reported a long-term response of 29% [40]. A double-blind randomized trial on the clinical effect of different shunt valve settings was also performed [41]; improvement after shunt surgery was evident within 3 months, irrespective of valve setting.…”
Section: Managementsupporting
confidence: 79%
“…However in a previous study where participants had low MMSE of 18 at baseline there was also no improvement in cognition after shunt placement [ 14 ]. This raises the possibility of MMSE not being a sensitive measure and perhaps more detailed cognitive testing should be performed similar to a small study of 37 participants [ 18 ] and another clinical trial of 68 participants [ 38 ] where a larger neuropsychological battery was able to capture differences. Additionally, the relatively short follow-up time (104 days) may not be sufficient to capture changes in clinical outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…8 They observed that programmable pressure valves were associated with fewer revision surgeries at 1 year; however, this effect was only substantiated in patients younger than 18 years. In that report, only 3 of the 11 studies evaluated included adult patients 6,7,14 and only one of the studies included adult hydrocephalus etiologies other than NPH. 14 A prospective study by Farahmand et al reported that nonprogrammable pressure valves were a risk factor for shunt revision within 6 months of initial implantation with an HR of 1.86 (95% CI 1.18-2.93).…”
Section: Discussionmentioning
confidence: 99%